2021
DOI: 10.4293/jsls.2021.00062
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Single-Port Donor Nephrectomy with the da Vinci SP® Surgical System

Abstract: Objectives: The da Vinci SP® Surgical System received U.S. Food and Drug Administration approval for urological procedures in 2018. Here, we describe the first experience performing single-port robot-assisted donor nephrectomy (RADN) using the da Vinci SP® surgical system, present 90-day clinical outcomes, and discuss tips for operative success. Methods: Seven consecutive patients underwent single-port RADN at a single institution between September 1, 2020 and March 31,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Overall, seven patients successfully underwent RADN, no major complications were reported, and mean hospitalization day was 2.1 days. 118…”
Section: Sp Robotic Nephroureterectomymentioning
confidence: 99%
“…Overall, seven patients successfully underwent RADN, no major complications were reported, and mean hospitalization day was 2.1 days. 118…”
Section: Sp Robotic Nephroureterectomymentioning
confidence: 99%
“…Well performed randomized controlled trials and meta-analyses are limited. [7][8][9][10][11][12][13][14] When implementing this new technique, one should be aware of the learning curve, which indicates longer operative times for the first RADN procedures; however, these times can improve over time. 8,15,16 At the Leiden University Medical Center (LUMC) Transplant Center, Leiden, the Netherlands, kidney, liver, (kidney) pancreas and islet of Langerhans transplantations are regularly performed.…”
Section: Introductionmentioning
confidence: 99%
“…7 Perhaps the most substantial recent development in the technique of living donor nephrectomies is the shift to minimally invasive procedures, speci cally the robot assisted living donor nephrectomy (RDN). [8][9][10] Studies have shown that RDN procedures have less blood loss and patients have less postoperative pain, lower risk of post-operative complications (surgical site infection and incisional hernia), and shorter hospital stays compared to their laparoscopic counterparts. [11][12][13] However, longer operative times have also been reported with RDN.…”
Section: Introductionmentioning
confidence: 99%